Analisis SWOT sebagai Alat Pengambilan Keputusan Bisnis di Era Digital dan Globalisasi - Avrilia Ayunia Widyaningrum; Destya Fitri Andini; Dian Putri Wulandari; Jihan Nur Afiyah; Lusiana Prastiwi; Rani Nur Azizah (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
In a rapidly evolving business world with the support of technology, companies must adopt effective strategies to stay competitive. One very helpful tool is SWOT Analysis or stands for Strengths, Weaknesses, Opportunities, Threats Analysis, which requires companies to identify internal strengths and external opportunities in order tol achieve comlpetitive advalntage. Thisl study aimls lto explore the role of SWOT Analysis in recognizing relevant strengths and opportunities for companies, assessing their impact on management decision making, and analyzing challenges and opportunities in their application in the digital era and globalization. SWOT analysis helps companies in designing effective strategies to achieve competitive advantage and maintain business continuity in the midst of fierce competition. The research method used is a systematic literature review, which includes the collection and analysis of data from various literatures. The results of the discussion show that SWOT Analysis is very important in helping companies formulate effective strategies by considering internal and external factors. In addition, the digital age and globalization bring challenges such as changing consumer preferences and increased competition, but also offer opportunities for market expansion and cross-border partnerships. Therefore, SWOT Analysis is an important tool in helping companies make strategic decisions to improve competitiveness in a dynamic global market.